LEVERAGING NANO-LEARNING INTO FASHION DESIGN CLASSROOM TIKTOK FOR FASHION VIDEOS - Maisalinia, Ria; Rahmawanti, Movi Riana; safitri, ani; saragih, enni erawati; Fatonah, Umi; Azhari, Farah Dilla (Program Studi Teknologi Pendidikan FKIP Universitas Ibn Khaldun, Bogor, 2024)
Nano-learning, a part of macro learning, involves small bursts of information into small video (approximately 60 seconds) has gained traction in educational matters. Tiktok, a social media platform known for short form videos, offer an excellent combination to integrate nano-learning into the fashion design classroom. This study explores the potentials of using Tiktok to deliver fashion design content in the classroom in a concise and engaging manner in education. Through a Descriptive Qualitative approach, involving an interview with 20 students who involve in Nano- learning, this study investigates the impact of Nano-learning with tiktok in enhancing students’ understanding of fashion design concepts. Participants were asked to examine their perception about the implementation of nano-learning with tiktok, and its impact to the education in general. Finding suggests that Tiktok Nano-learning is a promising tool for fashion design education in general. Students reported that the short- form video format that they made, made the content more accessible and engaging and enhance their understanding of fashion design concepts. They also appreciated the fact that the implementation of Nano-learning made them more creative and understand the content more. However the study also identified challenges, such as the potential for information overload, and the need for careful curation in the collection of the content. Overall the study demonstrated the potential of Tiktok Nano-learning to revolutionize fashion design education in summary. Leveraging the platform popularity and engaging format, educators can maximize the effective learning experiences that cate to the needs of the students for better classroom environment.